Evaluasi Hematologi Ikan Kakap Putih (Lates calcarifer) yang Diberi Pakan Mengandung Probiotik - Manik, Rina Ulicia (Jurnal Intek Akuakultur, 2026)
This research is about the effect of giving probiotic booster aquaenzyms to feed at different doses to look at the parameters of red blood cells, white blood cells and leukocyte differential. This study aims to analyze the effect of adding probiotic booster aquaenzyms in pelleted feed on blood hematological parameters of sea bass, with a focus on observing the number of erythrocytes, leukocytes and leukocyte differential. This research was conducted from May to June 2025 for 14 days at the Marine Aquaculture Lab, Aquaculture Study Program, Faculty of Marine Sciences, Raja Ali Haji Maritime University, Tanjungpinang. The research design used in this study used a Completely Randomized Design (CRD) with 4 treatments and 3 replications, namely control feed treatment without probiotic booster aquaenzyms and injected with bacteria, Treatment A feed with probiotic booster aquaenzyms 2 grams/kg feed every day and injected with bacteria, Treatment B feed with booster aquaenzyms 6 grams/kg feed every day and injected with bacteria, Treatment C with probiotic booster aquaenzyms 10 grams/kg of feed every day and challenge the Vibrio alginolyticus bacteria. The parameters observed during the research were, red blood cells (erythrocytes), white blood cells (leukocytes), leukocyte differential, survival rate, and water quality parameters. Data analysis used Microsoft Excel and data was analyzed using analysis of variance (ANOVA). Statistical analysis was carried out using SPSS software. If the data is significantly different (P<0.05), then Duncan's further test is carried out. The research results from the addition of probiotic booster aquaenzyms in pelleted feed were highest in treatment A with a dose of 2 grams/kg of feed on red blood cells and white blood cells. The differential leukocytes obtained during the study were lymphocytes and monocytes. The highest lymphocytes were obtained in treatment B, and the highest monocytes were obtained in treatment K. The highest survival rate was in treatment A.